The diadromous watersheds-ocean continuum: Managing diadromous fish as a community for ecosystem resilience - Ouellet, Valerie; Collins, Mathias J.; Kocik, John F.; Saunders, Rory; Sheehan, Timothy F.; Ogburn, Matthew B.; Trinko Lake, Tara (Frontiers in Ecology and Evolution, 2022)
Diadromous fishes play important ecological roles by delivering ecosystem services and making crucial connections along the watersheds-ocean continuum. However, it is difficult to fully understand the community-level impacts and cumulative benefits of diadromous fish migrations, as these species are most often considered individually or in small groups. Their interactions at a community level (e.g., interdependencies such as predation, co-migration, habitat conditioning) and the connections between their ecosystem roles and functions (e.g., cumulative marine-derived nutrient contributions, impacts on stream geomorphology) are yet to be fully understood. Similarly, freshwater, estuarine and marine ecosystems are often considered as independent parts, limiting understanding of the importance of connections across systems. We argue that by not considering the ecosystem interdependence and importance of diadromous fish as a community currently hinders the implementation of the large-scale management required to increase ecosystem resilience and fish productivity across the full range of these species. We developed a conceptual model, the Diadromous Watersheds-Ocean Continuum (DWOC), that uses ecosystem services to promote a more holistic approach to the management of the diadromous community and encourages an integrated understanding of the ecosystem connections made by these species. DWOC provides a framework for discussions that can help identify research and management needs, discuss the trade-offs of different management options, and analyze what pressing questions impede the implementation of large-scale management solutions towards a more ecosystem-based management approach.